1990
DOI: 10.1084/jem.171.3.801
|View full text |Cite
|
Sign up to set email alerts
|

Naive and memory T cells show distinct pathways of lymphocyte recirculation.

Abstract: In this report, we have addressed two questions concerning immunological memory: the way in which naive and memory T cells recirculate through the body, and the intrinsic rate of division within the naive and memory populations. We identified naive and memory T cells in sheep by their cell surface phenotype and their ability to respond to recall antigen. Memory T cells were CD2hi, CD58hi, CD44hi, CD11ahi, and CD45R-, as pertains in man. T cells that crossed from blood to the tissues of the hind leg and accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
441
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 729 publications
(467 citation statements)
references
References 52 publications
23
441
3
Order By: Relevance
“…The approach that we used is likely to underestimate the total numbers of MBP:87-99-reactive T cells present in the CNS because we isolated cells from the spinal cord only, and because during the cell isolation process from the spinal cord tissue we most likely do not recover all (or even the majority) of the infiltrating T cells. However, our assessment of the peripheral repertoire in the lymphoid tissues is also certainly an under representation of the total number of MBP: 87-99-specific cells outside the CNS (23,29). Because we always detected high frequencies of MBP:87-99-specific cells in the peritoneal cavity (representing a random extra lymphoid compartment from which T cells can be readily sampled), a considerable mass of the Ag-experienced memory/effector cells is likely to reside in other extra lymphoid tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…The approach that we used is likely to underestimate the total numbers of MBP:87-99-reactive T cells present in the CNS because we isolated cells from the spinal cord only, and because during the cell isolation process from the spinal cord tissue we most likely do not recover all (or even the majority) of the infiltrating T cells. However, our assessment of the peripheral repertoire in the lymphoid tissues is also certainly an under representation of the total number of MBP: 87-99-specific cells outside the CNS (23,29). Because we always detected high frequencies of MBP:87-99-specific cells in the peritoneal cavity (representing a random extra lymphoid compartment from which T cells can be readily sampled), a considerable mass of the Ag-experienced memory/effector cells is likely to reside in other extra lymphoid tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…Primed T cells can be phenotypically dissociated from naive cells by a number of alterations in surface marker expression. In mice these changes include the downregulation of CD45RB [106] and the concomitant up-regulation of CD44 and several adhesion molecules such as LFA-1 and VLA-4 which enhance their homing to peripheral tissues and sites of inflammation [107]. Whether such changes are reversible events or a stable phenotypical transformation that can be used to distinguish memory cells is a matter of much debate.…”
Section: Host Responses and Antigens Involved In Protective Immunity mentioning
confidence: 99%
“…Previous experiments have indicated that memory CD4 ϩ T cells are largely responsible for tissue-specific recirculation patterns observed using recirculating ELLs in vivo (23,26,27). To test for the possibility that a single lymphocyte subset was responsible for the observed tissue-specific homing patterns of PBLs, labeled lymphocytes were collected from efferent intestinal or s.c. lymph at 12, 24, and 36 h after i.v.…”
Section: ␥␦-T Cells Are the Major Recirculating Populationmentioning
confidence: 99%